Changes to the marketing strategy of the airline industry in Europe due to the proliferation of low-cost airlines in Europe - Keprta, Jan (2016)
The aim of this thesis is to analyze the changes to marketing strategy of airline companies in Europe due the proliferation of low-cost carriers in Europe. The thesis is divided into three parts. In the theoretical part the marketing strategy framework is established by reviewing the latest literature on marketing theory and its application to the airline industry. The second chapter provides the historical background and shows the specifics of the airline industry in order to determine when the proliferation of low-cost carriers in Europe occurred. It also analyzes the impact the proliferation had on the business operations of the network carriers by looking at the changes to different elements of the marketing mix. Finally the third chapter summarizes the authors research on consumer behavior in the airline industry. The research was conducted through a quantitative questionnaire and it investigates consumers perception of price and brand awareness.